Machine learning algorithms in sepsis - Agnello, Luisa; Vidali, Matteo; Padoan, Andrea; Lucis, Riccardo; Mancini, Alessio; Guerranti, Roberto; Plebani, Mario; Ciaccio, Marcello; Carobene, Anna (Clinica chimica acta, 2024)
•Machine learning models are promising for the early diagnosis and prognosis of sepsis.•There is still high heterogeneity among studies.•The appropriate interpretation by a multidisciplinary approach, including professionals with different skills, is mandatory. Sepsis remains a significant global health challenge due to its high mortality and morbidity, compounded by the difficulty of early detection given its variable clinical manifestations. The integration of machine learning (ML) into laboratory medicine for timely sepsis identification and outcome forecasting is an emerging field of interest. This comprehensive review assesses the current body of research on ML applications for sepsis within the realm of laboratory diagnostics, detailing both their strengths and shortcomings. An extensive literature search was performed by two independent investigators across PubMed and Scopus databases, employing the keywords “Sepsis,” “Machine Learning,” and “Laboratory” without publication date limitations, culminating in January 2023. Each selected study was meticulously evaluated for various aspects, including its design, intent (diagnostic or prognostic), clinical environment, demographics, sepsis criteria, data gathering period, and the scope and nature of features, in addition to the ML methodologies and their validation procedures. Out of 135 articles reviewed, 39 fulfilled the criteria for inclusion. Among these, the majority (30 studies) were focused on devising ML algorithms for diagnosis, fewer (8 studies) on prognosis, and one study addressed both aspects. The dissemination of these studies across an array of journals reflects the interdisciplinary engagement in the development of ML algorithms for sepsis. This analysis highlights the promising role of ML in the early diagnosis of sepsis while drawing attention to the need for uniformity in validating models and defining features, crucial steps for ensuring the reliability and practicality of ML in clinical setting.